Poorly differentiated synovial sarcoma in the wrist - Case report - Daniela Cristina Caetano Maia; Carla Kellen da Silva Menezes; Thales Costa Bastos; Luiz Carlos de Lima Ferreira; Fabio Francesconi (Sociedade Brasileira de Dermatologia, 2014)
Synovial sarcomas are rare malignant tumors affecting mainly young adults, presenting as a slow growth mass located in deep soft tissues of extremities, near the joints. In this report a 34-year-old male patient, presented an ulcerovegetative lesion on the right wrist which was completely excised. Histopathology and immunohistochemistry confirmed synovial sarcomas with poorly differentiated cells. This patient presented 11 months later with ipsilateral axillary lymph node metastasis, which emphasizes the unfavorable prognosis of this synovial sarcoma variant. The indolent growth pattern of this sarcoma justifies the well circumscribed initial stages, which progressively infiltrate adjacent structures with lung metastasis (80%) and lymph node involvement (20%) and thus corroborates the importance of early diagnosis and proper treatment.